PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, DAN HARAPAN DOSEN TERHADAP KEPUASAN KERJA - Saur Mangapul Tampubolon (Universitas Negeri Jakarta, 2010)
The objectives of this research is to find out the effects of leadership style, work environment, and the lecturers or teaching staff satisfaction. The research has been conducted at Pakuan University, Bogor. The method used was a survey with data analysis of path analysis. The respondents were 72 out of 264 total teaching staff in the university. They were selected at random. The research finding are as the followings: (1) leadership style has a direct effect on the lecturer’s satisfaction, (2) and also on the work environment has a direct effect on the job satisfaction, (3) the expectation gives a direct effect on job satisfaction, but the leadership style gives and indirect effect on job satisfaction, but the leadership style gives an indirect effect on job satisfaction through expectation, and (4) the working environment has also indirect effect on the job satisfaction through expectation. The conclusion is that the lecturer’s satisfaction is affected by the leadership style, work environment and the lecturer’s expectation.